Moth Flame Optimization Method for Unified Power Quality Conditioner Allocation - M. Laxmidevi Ramanaiah; M. Damodar Reddy (Institute of Advanced Engineering and Science, 2018)
This paper introduces a new optimization method to determine the optimal allocation of Unified Power Quality Conditioner (UPQC) in the distribution systems. UPQC is a versatile Custom Power Device (CPD) to solve problems related to voltage and current by the series and shunt compensator in the distribution systems. The task of UPQC highlighted in this paper is the required load reactive power is provided by both the series and shunt compensators. The UPQC’s steady state compensation capability has given a solution for providing reactive power compensation in large distribution systems. The optimization method adopted is Moth Flame Optimization (MFO). The best location and series compensator voltage are determined using MFO. The voltage injected by the series compensator and reactive power injected by the shunt compensator is incorporated in the load flow method. The effectiveness of the proposed method is validated with standard distribution systems.